Comparison of the Legal Construction of Hadhanah Rights in Saudi Arabia, Turkey and Indonesia - Yudhantara Syahputra, Dian; Zuhdi, Syaifuddin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
Hadhanah is an act that must be carried out by their parents, because without hadhanah it will result in the child becoming abandoned and his life will be wasted. Fiqh scholars agree that the principle of caring and educating is an obligation for parents, because if children are still young, it will have a damaging effect on the child and their future can even threaten the existence of their soul. This study aims to investigate and analyze the protection of hadhanah rights in three countries, namely Saudi Arabia, Turkey, and Indonesia. This research will use normative research methods. The results of this research are hadhanah rights in Islam in Saudi Arabia, Turkey, and Indonesia. Saudi Arabia, with its legal system based on the Hambali madhhab, emphasizes the protection, education, and custody of children supervised by Islamic authorities. Turkey, with its more moderate civil law, ensures the fulfillment of children's rights in divorce decisions, with attention to the protection, care, and education of children. In Indonesia, the Marriage Law and the Compilation of Islamic Law affirm the protection and maintenance of children in accordance with the principle of Islamic hadhanah rights. Turkey is considered more responsive to the changing times by integrating modern values in the protection of children's rights, followed by Indonesia's progressive adaptation. The contribution of this research is that this analysis is expected to provide in-depth insights into the development and implementation of Islamic family law in various countries with different backgrounds.